2013
DOI: 10.1007/s11606-013-2409-1
|View full text |Cite
|
Sign up to set email alerts
|

Drinking Patterns of Older Adults with Chronic Medical Conditions

Abstract: BACKGROUND: Understanding alcohol consumption patterns of older adults with chronic illness is important given the aging baby boomer generation, the increase in prevalence of chronic conditions and associated medication use, and the potential consequences of excessive drinking in this population. OBJECTIVES: To estimate the prevalence of alcohol consumption patterns, including at-risk drinking, in older adults with at least one of seven common chronic conditions. DESIGN/METHODS: This descriptive study used the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 50 publications
4
18
1
1
Order By: Relevance
“…46 In fact, in one study in Northern Europe, 20% of older adults consuming alcohol reported doing it for "medical purposes." 47 As in our study, previous research has found that suboptimal self-rated health 30,48 and functional limitations 30,44,47,48 were associated with lower frequency of alcohol consumption, particularly heavy intake. We found that limitations in IADL are associated with a higher frequency of ex-drinkers and with a nonstatistically significant tendency to lower frequency of moderate and heavy drinkers.…”
Section: Discussionsupporting
confidence: 74%
“…46 In fact, in one study in Northern Europe, 20% of older adults consuming alcohol reported doing it for "medical purposes." 47 As in our study, previous research has found that suboptimal self-rated health 30,48 and functional limitations 30,44,47,48 were associated with lower frequency of alcohol consumption, particularly heavy intake. We found that limitations in IADL are associated with a higher frequency of ex-drinkers and with a nonstatistically significant tendency to lower frequency of moderate and heavy drinkers.…”
Section: Discussionsupporting
confidence: 74%
“…The prevalence of alcohol consumption among adults with chronic medical conditions in the U.S. is ;31% (19). In our study of an ethnically diverse population of patients with type 2 diabetes, the level of alcohol consumption was similar.…”
Section: Previous Studiesmentioning
confidence: 46%
“…Compared to elderly Finns in general, alcohol abuse was 4.5 fold more frequent among women and 2.3 fold more frequent among men with COPD [41]. Excess alcohol use has been found also in other COPD populations [42]. Data on chronic atrial fibrillation and diffusing capacity were not available for all, but the univariate model suggested that chronic atrial fibrillation would harm HRQoL (crude OR 2.4, 95% CI 1.00-6.0, p ≤ 0.05), while impaired diffusing capacity did not.…”
Section: Discussionmentioning
confidence: 99%